Reconstitution and Minimization of a Micrococcin Biosynthetic Pathway in Bacillus subtilis - Bennallack, Philip R. (J Bacteriol, 2016)
Thiopeptides represent one of several families of highly modified peptide antibiotics that hold great promise for natural product engineering. These macrocyclic peptides are produced by a combination of ribosomal synthesis and extensive posttranslational modification by dedicated processing enzymes. We previously identified a compact, plasmid-borne gene cluster for the biosynthesis of micrococcin P1 (MP1), an archetypal thiopeptide antibiotic. In an effort to genetically dissect this pathway, we have reconstituted it in Bacillus subtilis. Successful MP1 production required promoter engineering and the reassembly of essential biosynthetic genes in a modular plasmid. The resulting system allows for rapid pathway manipulation, including protein tagging and gene deletion. We find that 8 processing proteins are sufficient for the production of MP1 and that the tailoring enzyme TclS catalyzes a C-terminal reduction step that distinguishes MP1 from its sister compound micrococcin P2. IMPORTANCE The emergence of antibiotic resistance is one of the most urgent human health concerns of our day. A crucial component in an integrated strategy for countering antibiotic resistance is the ability to engineer pathways for the biosynthesis of natural and derivatized antimicrobial compounds. In this study, the model organism B. subtilis was employed to reconstitute and genetically modularize a 9-gene system for the biosynthesis of micrococcin, the founding member of a growing family of thiopeptide antibiotics.